A Model of Fish Consumption Among Indonesian Youth with the Moderation on Their Perception of Fish Quality Assurance - Ika Nur Putriantini; Aldino Dityanawarman; Inaiyah Inaiyah; Hafit Rahman (Universitas Gadjah Mada, 2022)
This study provides a relevant examination of fish consumption among Indonesian youth; it contributes to their perception of fish quality assurance. A cross-sectional sample of Indonesian youth scholars between 17 and 26 years old (n = 1.163) responded to an online questionnaire validly from February to March 2021. Structural equation modelling was used to estimate the direction and strength of relationships between variables. The results demonstrate that fish availability, health involvement, fish consumption in childhood, sensory beliefs, and price correlated significantly with fish consumption among Indonesian youth, but that relationship was mediated by attitude to consume fish. Social pressure also has a significant correlation to fish consumption among Indonesian youth. Meanwhile, we found that Indonesian youth's perception of fish quality assurance negatively moderates the relationship between fish and fish consumption. This perception of fish quality assurance is likely not to affect the real-world relationship between the desire to consume fish and fish consumption. Understanding the role different variables play in their fish consumption habits may provide helpful insights for the government to develop strategies for increasing the final goal, which is the intake of fish among young consumers.